2013
DOI: 10.1021/ja404285b
|View full text |Cite
|
Sign up to set email alerts
|

Co-Catalyzed Cross-Coupling of Alkyl Halides with Tertiary Alkyl Grignard Reagents Using a 1,3-Butadiene Additive

Abstract: The cobalt-catalyzed cross-coupling of alkyl (pseudo)halides with alkyl Grignard reagents in the presence of 1,3-butadiene as a ligand precursor and LiI is described. Sterically congested quaternary carbon centers could be constructed by using tertiary alkyl Grignard reagents. This reaction proceeds via an ionic mechanism with inversion of stereochemistry at the reacting site of the alkyl halide and is compatible with various functional groups. The use of both 1,3-butadiene and LiI was essential for achieving … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
70
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 115 publications
(76 citation statements)
references
References 52 publications
3
70
1
2
Order By: Relevance
“… The formation of anionic cobaltate complexes as central intermediates of the title reaction, as suggested by Kambe and co‐workers …”
Section: Introductionmentioning
confidence: 57%
“… The formation of anionic cobaltate complexes as central intermediates of the title reaction, as suggested by Kambe and co‐workers …”
Section: Introductionmentioning
confidence: 57%
“…The Grignard reagents used in this study were purchased or prepared as diethyl ether (Et2O) solutions. [32][33][34][35] GC yield (%) Under these optimized conditions, the scope of Grignard reagents was investigated ( Figure 2). Initial ligand screening revealed that neither tricyclohexylphosphine (PCy3) nor 1,3dicyclohexylimidazol-2-ylidene (ICy), which are reported to be the most effective ligands for C(aryl)-O bond activation, 15,16 efficiently formed the desired cross-coupling product 1a with most of 1 being recovered (entries 1 and 2 in Table 1a).…”
mentioning
confidence: 99%
“…Primary alkyl Grignard reagents gave the corresponding coupling products in good yields (Table 1, entries 11 and 12), but methylmagnesium chloride (MeMgCl) and phenylmagnesium bromide (PhMgBr) reacted sluggishly, due to difficulties in generating the active catalytic species (Table 1, entries 13 and 14). 5 The relative reactivity of n-, sec-and tertbutyl Grignard reagents was estimated to be roughly 1:4:0.6, by competitive experiments.…”
Section: N-oct-brmentioning
confidence: 99%
“…3 During the course our studies on transition-metal-catalyzed cross-couplings using unsaturated hydrocarbon additives, 3d,e,4 we found that cobalt salts, with the aid of lithium iodide (LiI) and conjugated diene additives such as 1,3-butadiene or isoprene, catalyze successfully cross-coupling reactions of alkyl (pseudo)halides with tertiary alkyl Grignard reagents giving rise to the formation of quaternary carbon centers, where esters, amides, carbamates and acetal functional groups were well tolerated. [5][6][7] It was also possible to couple primary and secondary alkyl Grignard reagents with alkyl halides using this catalyst system. The reactions Scheme 1 General procedures for the cobalt-catalyzed cross-coupling reaction of alkyl halides with alkyl Grignard reagents (Procedures 1 and 2), a reaction using 0.1 mol% of catalyst (Procedure 3) and a large-scale reaction (Procedure 4) + CoCl 2 (2 mol%), LiI (4 mol%)…”
Section: Introductionmentioning
confidence: 99%